Transformasi Perpustakaan Universitas Andalas menuju Learning Commons: Studi Perspektif Pengguna - Putri, Regina; Marlini, Marlini; Desriyeni, Desriyeni (Lembaga Yasin AlSys, 2025)
The transformation of academic libraries into learning commons models is a response to changing learning patterns and technological developments that require collaborative, flexible, and technology-integrated learning spaces, including in the context of the Universitas Andalas Library, which must accommodate a large user base and provide inclusive, technology-based learning facilities. This study aims to analyze the transformation of the Universitas Andalas Library towards a learning commons model from the users’ perspective by examining the factors that influence its relevance and success. A qualitative approach was employed using a literature study method by reviewing and interpreting scholarly literature, research reports, and institutional documents that discuss the transformation of academic libraries in Indonesia. The findings indicate that the learning commons model strengthens the role of the library as a center of active learning through the integration of physical spaces, digital technologies, and collaborative services; however, its implementation still faces challenges related to infrastructure limitations, the need to improve librarians’ competencies and training, and users’ adaptation to new learning cultures. The study concludes that the successful implementation of a learning commons is highly dependent on its alignment with institutional contexts and user needs, and its implications provide a conceptual basis for developing library transformation strategies that support collaborative learning, digital literacy, and academic innovation in Indonesian universities.